2007
DOI: 10.1253/circj.71.220
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Endothelial Vasomotor Function After Sirolimus-Eluting Stent Implantation

Abstract: he sirolimus-eluting stent (SES) is a stent coated with sirolimus, and is reported to prevent neo-intimal proliferation and injury-induced arterial intimal thickening. 1 It is widely used to treat coronary stenotic lesions because of the associated very low rates of in-stent restenosis and need for target lesion revascularization compared with conventional bare metal stents (BMS). [2][3][4] Sirolimus is a macrolide antifungal agent with antiproliferative and immunosuppressant properties. It inhibits vascular s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
82
2
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(90 citation statements)
references
References 26 publications
5
82
2
1
Order By: Relevance
“…[13][14][15] Recent studies also suggest that DESs may result in endothelial dysfunction manifested through impaired vascular responsiveness in the downstream vessel as well as contributing to late stent thrombosis through neoatherosclerosis. [16][17][18] However, several studies also suggest that cell-cycle inhibitors may possess antiatherogenic properties. [19][20][21][22][23] Although published data are conflicted, it appears that overall outcomes, including target vessel revascularization rates, are slightly more favorable in patients receiving DES, although this has to be weighed against higher stent costs and the necessity for prolonged, uninterrupted antiplatelet therapy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[13][14][15] Recent studies also suggest that DESs may result in endothelial dysfunction manifested through impaired vascular responsiveness in the downstream vessel as well as contributing to late stent thrombosis through neoatherosclerosis. [16][17][18] However, several studies also suggest that cell-cycle inhibitors may possess antiatherogenic properties. [19][20][21][22][23] Although published data are conflicted, it appears that overall outcomes, including target vessel revascularization rates, are slightly more favorable in patients receiving DES, although this has to be weighed against higher stent costs and the necessity for prolonged, uninterrupted antiplatelet therapy.…”
Section: Resultsmentioning
confidence: 99%
“…Although this result is not expected with respect to a variety of studies demonstrating endothelial dysfunction in vessels treated with DES and neoatherosclerosis of the target lesion, the notion that antiproliferative agents could have an atheroprotective effect is not without precedent. 16,17 Multiple studies have demonstrated the atherosclerotic attenuation of sirolimus in Apolipoprotein E-deficient mice and human vascular smooth muscle cells. [19][20][21][22] A variety of studies investigating coronary artery disease in heart transplant patients, who have baseline endothelial dysfunction, have shown that antiproliferatives such as sirolimus attenuate the rate of atherosclerotic progression.…”
Section: Discussionmentioning
confidence: 99%
“…Although sirolimus, a potent immunosuppressive agent, possesses anti-inflammatory and antiproliferative effects, the drug may also impair endothelium regeneration and normal endothelial functions, 21,22) including the production of essential anti-inflammatory and antithrombotic factors. Thus, it is possible that sirolimus contributes toward creating a proinflammatory environment.…”
Section: Discussionmentioning
confidence: 99%
“…Data from clinical trials suggested that after implantation of first generation of DES (sirolimus and paclitaxel), endothelium-dependent vasorelaxation is impaired (evaluated by intracoronary infusion of acetylcholine followed by bolus injection of nitrate and angiographic assessment of the artery segments adjacent to the implanted stent) (67)(68)(69)(70). More recent data suggested that second generation DES (everolimus-eluting, biolimus-eluting, zotarolimus eluting) do not cause this effect (71)(72)(73).…”
Section: Restoring Vasomotionmentioning
confidence: 99%